2010
DOI: 10.1158/0008-5472.can-10-0303
|View full text |Cite
|
Sign up to set email alerts
|

Visible Drug Delivery by Supramolecular Nanocarriers Directing to Single-Platformed Diagnosis and Therapy of Pancreatic Tumor Model

Abstract: Nanoparticle therapeutics are promising platforms for cancer therapy. However, it remains a formidable challenge to assess their distribution and clinical efficacy for therapeutic applications. Here, by using multifunctional polymeric micellar nanocarriers incorporating clinically approved gadolinium (Gd)-based magnetic resonance imaging contrast agents and platinum (Pt) anticancer drugs through reversible metal chelation of Pt, simultaneous imaging and therapy of an orthotopic animal model of intractable huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 39 publications
1
79
0
2
Order By: Relevance
“…17 Our results showed that the injection of Gd-DTPA/DACHPtloaded micelles modified the enhancement pattern in the liver. Tumor signal intensity was enhanced from hypointense to markedly hyperintense.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…17 Our results showed that the injection of Gd-DTPA/DACHPtloaded micelles modified the enhancement pattern in the liver. Tumor signal intensity was enhanced from hypointense to markedly hyperintense.…”
mentioning
confidence: 55%
“…17 Briefly, Gd-DTPA (SigmaAldrich Japan, Tokyo, Japan) was converted to sodium salt by adjusting the pH to 7 with NaOH, and lyophilized. A 5 mmol/L solution of bis(nitrato) (trans-l-1,2-diaminocyclohexane)platinum(II) [DACHPt(NO 3 ) 2 ; W.C. Heraeus GmbH & Co. KG, Hanau, Germany] in water was mixed with the sodium salt of Gd-DTPA (5 mmol/L), and the solution was maintained for 24 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations